(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article analyzes the Assembly of the People of Kyrgyzstan (APK), dedicated to the problems of formation and operation of national cultural centers. The accumulated factual material allows us to consider these issues in a complex of historical approaches and directions.